220k views
3 votes
What equation is equivalent to 3x+6=4x+7

User Kingbase
by
5.0k points

2 Answers

4 votes

Final answer:

To find an equation equivalent to 3x+6=4x+7, isolate x by subtracting 3x and 7 from both sides, yielding x = -1. Therefore, the two equations are equivalent as they result in the same solution for x.

Step-by-step explanation:

The equation 3x+6=4x+7 can be solved by isolating the variable x. To find an equivalent equation, you can move terms involving x to one side and constant terms to the other side. Follow these steps:

  1. Subtract 3x from both sides of the equation to get: 6 = x + 7.
  2. Then, subtract 7 from both sides of the equation to isolate x: x = -1.

This shows that the value of x that satisfies both equations is x = -1. Thus, both equations are equivalent because they have the same solution.

User Maxali
by
5.4k points
6 votes

Answer:

x=-1

Step-by-step explanation:

The first thing we can do is subtract 3x from both sides (it makes solving the equation easier if you get rid of the variable first).

3x+6=4x+7

-3x -3x

6=x+7

All we need to do now is subtract 7 on both sides.

6=x+7

-7 -7

-1=x or x=-1 (they both mean the same thing!)

Hope this helps!! Have a wonderful day c:

User SachinJose
by
4.5k points